Modeling the Impact of Shocks on Fluctuations in the Exchange Rate of Remittances in the Syrian Pound against the US Dollar - شفيق اسماعيل رولى (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This research aims to model the effect of shocks in studying the fluctuations of the exchange rate of remittances in Syria, where the researcher modeled the fluctuations of the exchange rate of remittances in the Syrian pound against the US dollar, for a series of monthly data during the period from February 2012 to August 2023. The descriptive analytical approach based on analyzing the impact of shocks on exchange rates was relied upon using ARIMA and GARCH econometric models. The most important results of the research were that the monthly series of the exchange rate of remittances in the Syrian pound against the US dollar showed that it is stable at the first difference, with fluctuations starting from March 2020. After the process of comparison between the models, it was concluded that the model ARIMA(0,1,1) is the model that generates the series, and that the model GARCH(1,1) is the model that generates fluctuations.